Phytoestrogens: Implications in Neurovascular Research - Lephart, Edwin D.; Porter, James P.; Hedges, Dawson W.; Lund, Trent D.; Setchell, Kenneth D.R. (Current Neurovascular Research, 2004)
The early discontinuation of the Women's Health Initiative trial evaluating the effects of estrogen plus progestin due to concerns about the risk-benefit ratio of this steroid combination therapy emphasizes the need to examine alternative methods of estrogen replacement. One such alternative is isoflavone consumption of soy-derived dietary phytoestrogens that have received prevalent usage due to their ability to decrease age related disease (cardiovascular and osteoporosis), hormone-dependent cancers (breast and prostate), and peri- and postmenopausal symptoms. Differences in dietary phytoestrogen consumption result in large variations in somatic phytoestrogen content. These molecules affect estrogen and estrogen receptor function in several ways, including having both agonist and antagonist effects on estrogen receptors, as well as functioning like natural selective estrogen receptor modulators. Similar to estrogens, dietary phytoestrogens appear to affect certain aspects of vascular, neuroendocrine, and cognitive function. This article reviews health effects of estrogen, isoflavones and their hormonal mechanism of action, brain penetration by isoflavones, heath effects of isoflavones, and effects of isoflavones on vascular, neuroendocrine, and cognitive function. Because of their diverse health effects and widespread availability in soy foods, dietary phytoestrogens merit continued research into their effects on human health and cognitive function.
Keywords: selective estrogen receptor modulators